Analisis Dampak Lingkungan melalui Life Cycle Assessement (LCA) di Industri Keramik Mojokerto - Novirina Hendrasarie; Rahmadini Luchmanandri (Prosiding ESEC, 2023)
Ceramics are products made from clay orclay through several stages of production. Ceramic production apart from having a positive impact primarily in the economic field also has a negative impact on the environment. Life Cycle Assessement (LCA) is a method of measuring the impact on the environment in a production process. The purpose of this research is to determine the environmental impact resulting from the process of making ceramics at the Mojokerto Ceramics Factory. The research carried out analyzed the ceramic production process so that the scope of LCA used wasgate to gate with a production period of 1 day. The research results show that impactglobal warming the highest was caused by gas distribution (762700 kg CO2 eq) and on processglaze preparation amounting to (477.6 kg CO2 eq). In the impact categoryacidification, the highest impact was caused by gas distribution of (3892 kg SO2 eq) and on processfiring of (3.362 kg SO2 eq). Impact categoryhuman toxicity, the highest impact was caused by gas distribution (72620 kg 1.4 DB eq) and processfiring of (1357 kg 1.4 DB eq). Improvements that can be made are by reducing the use of gas by utilizing alternative energy or incineration technology.